COMPANY SIZE MODERATES SALES GROWTH AND PROFITABILITY ON EARNINGS MANAGEMENT - Kosasih, Kosasih; Chairunisa, Mariyam; Riawati, Neneng (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
This study aims to analyze the effect of sales growth, profitability, and company size on earnings management empirical study of manufacturing companies in the goods & consumer industry sector listed on the Indonesia Stock Exchange for the period 2023 - 2023. The researcher used a quantitative method with secondary data sources. The method used is purposive sampling. The population in this study was 119 companies and 34 companies were selected as research samples with the amount of data to be used for 4 years being 136 data. This study uses descriptive analysis techniques, classical assumption tests, model feasibility tests, and multiple linear analysis tests with the help of SPSS data processing applications. The results of the study show that sales growth has an effect on earnings management, but profitability has no effect on earnings management. Company size weakens the relationship between sales growth and profitability on earnings management.